To end all wars : a story of loyalty and rebellion, 1914-1918 - Hochschild, Adam (Boston : Houghton Mifflin Harcourt, 2011)
Presents a history of World War I, focusing on the moral conflict between the proponents of the war and its critics in Great Britain.
Includes bibliographical references (p. [379]-422) and index.
Keywords: World War, 1914-1918 -- Great Britain; World War, 1914-1918 -- Social aspects -- Great Britain; Soldiers -- Great Britain -- Biography; Conscientious objectors -- Great Britain -- Biography; Loyalty -- Case studies; World War, 1914-1918 -- Psychological aspects; World War, 1914-1918 -- Moral and ethical aspects; Militarism -- History -- Great Britain -- 20th century; Pacifism -- History -- Great Britain -- 20th century; World War, 1914-1918 -- Great Britain; World War, 1914-1918 -- Social aspects -- Great Britain; Soldiers -- Great Britain -- Biography; Conscientious objectors -- Great Britain -- Biography; Loyalty -- Case studies; World War, 1914-1918 -- Psychological aspects; World War, 1914-1918 -- Ethical aspects; Military policy -- Great Britain -- History; Pacifism -- Great Britain -- History